(untitled) (Mediscope, 2025)
Introduction: Menopause means the permanent cessation of menstruation at the end of reproductive life due to loss of ovarian follicular activity. The age of menopause ranges between 45 -55 years, the average being 50 years. It has become a major public health concern around the world. Objectives: The aim was to reveal the common health problems and the remedial measures adopted by women in the post-menopausal stage. At the same time attempt was made to explore the relationship between post-menopausal symptoms with other factors like age of menarche, socioeconomic condition, conjugal life, and contraception. Methods: A cross-sectional study was conducted in a suburban area of Chattogram among 208 post-menopausal women. Data were collected through face-to-face interviews using an interview schedule. Results: A total of 208 (55.85%) postmenopausal women experienced at least one or more menopausal symptom(s). The most common complaints of post-menopausal women were hot flush (43.3%), joint pain (19.3%), insomnia (16.6%) & night sweats (14.5%). Among the respondents who seek health care services, the majority of the respondents consult the pharmacy directly rather than the hospital for psychological & urogenital problems, but 70.2% of respondents were found to be consulted in the hospital for somatic problems. Conclusion: The study findings revealed that the majority of the respondents were ignorant regarding health problems in menopause, so it is necessary to critically introspect the health needs of postmenopausal women and specific components that can be incorporated into the national health programs. Mediscope 2025;12(2): 54-59